Environmental fate of five brominated flame retardants co-exposure in a water-sediment-zebrafish microcosm system: Enrichment, removal, and metabolism mechanisms. (10th February 2023) - Qiao, Zhihua; Wang, Yawen; Lu, Cong; Ling, Siyuan; Zhou, Shanqi; Fu, Mengru; Luo, Kailun; Peng, Cheng; Zhang, Wei; Zhou, Bingsheng
Abstract: Brominated flame retardants (BFRs) are widely used in electronic products. After electronics obsolescence, BFRs are gradually released and enriched in the environment, thus leading to frequent occurrence and detection. However, the environmental fate of multiple flame retardants in aquatic microcosms has not been explored, and it mainly focused on the environmental monitoring of BFRs and the toxicity of a single BFR to aquatic organisms. To fill the gap, based on actual investigation, a water-sediment-zebrafish microcosm system was co-exposed to five concentrations (0.2, 1, 5, 25, and 50 mg/kg) of pentabromotoluene (PBT), hexabromobenzene (HBB), 1, 2-bis(2, 4, 6-tribromophenoxy) ethane (BTBPE), decabromodiphenyl ethane (DBDPE), and decabromodiphenyl ether (BDE-209) for the enrichment (35 days) and clearance (10 days) experiments. The results showed that the liver, intestine, and gill were the top three tissues enriched in BFRs, which were 7504.54, 6936.99, and 3532.97 ng/g, respectively. BFRs can also be transferred between a generation. The compositions of BFRs in the tissues of zebrafish were also different, and the average compositions of DBDPE and BDE-209 were 36.2% and 28.6%, respectively, indicating that DBDPE and BDE-209 were more easily absorbed by zebrafish. Additionally, the average scavenging half-lives of PBT, HBB, BTBPE, DBDPE, and BDE209 were 4.01, 4.09, 2.90, 3.72, and 3.75 days, respectively, suggesting that these chemicals barely lasted long in zebrafish. The metabolic pathways of the five BFRs were also probed, and gradual debromination occurred in the organisms. These observations would provide a basis for the study of the fate and toxicology of BFRs in the water environment. Graphical abstract: Image 1 Highlights: Enrichment ability of liver, intestine and gills to the BFRs were the first three. The BFRs can be transferred to the next generation. Zebrafish had a strong scavenging ability to the BFRs. Zebrafish can metabolize the BFRs through progressive debromination.